Предмет: Математика,
автор: Nikky756
(3a-1)(2a+1)-(3a-1)^2 при а=0,3 плеес
Ответы
Автор ответа:
0
(3а - 1)(2а + 1) - (3а -1)^2 = 6a^2 - 2a +3a - 1 - 9a^2 +6a -1 =
= - 3a^2 + 7a - 2 → при а = 0,3 → = -3*0,09 + 7*0,3 - 2 = - 0,27+3,1-2 =
= 3,1 - 2,27 = 0,83
= - 3a^2 + 7a - 2 → при а = 0,3 → = -3*0,09 + 7*0,3 - 2 = - 0,27+3,1-2 =
= 3,1 - 2,27 = 0,83
Похожие вопросы
Предмет: Биология,
автор: andriy02122007a
Предмет: Українська мова,
автор: 2345678234567778
Предмет: География,
автор: druzinila90
Предмет: Математика,
автор: dilbaribrahimov
Предмет: Литература,
автор: немчинова